Pentingnya Sertifikasi Halal sebagai Nilai Tambah dan Legalitas Produk Usaha Mikro, Kecil, dan Menengah (UMKM) - Laelasari, Eda; Rudiansyah, R.; Saputra, Diva; Ruswandi, Irvan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The importance of this halal certificate also has a strong legal basis. Based on Law Number 33 of 2014 concerning Halal Product Assurance (JPH), every product that enters, circulates, and is traded in the territory of Indonesia must be halal certified. This regulation is further reinforced through derivative regulations such as Government Regulation Number 31 of 2019, which governs the implementation of the law. The socialization of the halal certification program for UMKM actors is not only focused on the number of socialization participants but more on understanding, awareness, and changes in community behavior. This approach also allows students to provide more targeted assistance, as every UMKM actor has different conditions and needs. The halal certificate for all UMKM products is very important, yet after exploring information related to their knowledge of halal certification, it was found that many UMKM actors still do not understand the importance of halal assurance for their products. The implementation of the halal certificate program was carried out as part of a student community service initiative by IAI Nasional Laa Roiba during a Community Service Program (Kuliah Kerja Nyata) in Bogor Regency. The method used was a qualitative approach with door-to-door techniques and direct interviews. Students conducted interviews with UMKM actors and community leaders, ensuring that the information obtained was more in-depth, accurate, and aligned with the real conditions on the ground. The halal certification socialization activity for UMKM in Tonjong Village on August 25, 2025, ran well and effectively. The results of the activity showed an increase in the knowledge and awareness of UMKM actors regarding the importance of halal certification, from both a religious and economic perspective. The community's response was very positive, marked by high participation, enthusiasm, and several business owners immediately consulting on the registration process.